Length and Depth of the Central Sulcus: A Postmortem Study (Bangladesh Journal of Anatomy, 2014)
Context: The central sulcus, which is located between the primary motor and primary somatic sensory cortex is an important structure and landmark of the cerebral hemisphere. Morphology of the central sulcus varies with age, sex, manual skill, handedness and in many diseases. This study is carried out to establish a normal standard in different age groups in length and depth of the central sulcus. Materials and Methods: A cross-sectional, analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, on one hundred and forty (140) on human cerebral hemispheres. The samples were divided into four different age groups i.e. Group A (20-29 years), Group B (30-39 years), Group C (40-49 years) and Group D (50-59 years). All the samples were studied morphologically. Results: The mean length of central sulcus was 102.89±3.55 mm to 96.83±3.92 mm in male and 98.00±5.17 mm to 96.29±2.56 mm in female. Depth of the central sulcus was 20.02±2.41 mm to 21.50±2.21 mm in male and 20.50±2.57 mm to 21.36±1.87 mm in female. The difference in mean length of the right central sulcus between male and female was statistically significant in group A (p